Synthesis, Characterization and Immunoassay of The Artificial Antigen for Cadmium(II) - Guo, Ming; Pang, Shuo-Quan (Asian Journal of Chemistry, 2010)
Artificial antigens Cd-IEDTA-BSA (HSA) were synthesized using the bifunctional chelating agent IEDTA (isothiocyanobenzylethyl enediamine tetraacetic acid) coupling with cadmium and protein carrier. The artificial antigens were characterized by atomic absorption spectroscopy, ultraviolet spectrum, sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and 2,4,6-trinitrobenzenesulfonic acid (TNBS) spectrometry and the comparison was taken among these methods. The animal immune was also done to verify immune effect of the artificial antigen. The consistent corroboration by these methods showed that the artificial antigen was synthesized successfully and the coupling rate of Cd-IEDTA-BSA, Cd-IEDTA-HSA were 11-13:1 and 14-16:1, respectively. The substitution extent of free amino groups for the artificial antigen was 23.12 % for Cd-IEDTA-BSA, 29.17 % for Cd-IEDTA-HSA. The experiment of animal immune indicated that the specific antiserum was generated after immunization of BALB/c mice with Cd-IEDTA-BSA and the titer of the antiserum reached the level of 12800:1. This work provides a helpful reference for further research of preparation on monoclonal antibodies against heavy metals.